Synthesis of covalent bonding MWCNT-oligoethylene linezolid conjugates and their antibacterial activity against bacterial strains. Issue 46 (31st August 2021) - Alatorre-Barajas, José A.; Alcántar-Zavala, Eleazar; Gil-Rivas, M. Graciela; Estrada-Zavala, Edgar; Ochoa-Terán, Adrián; Gochi-Ponce, Y.; Montes-Ávila, Julio; Cabrera, Alberto; Trujillo-Navarrete, Balter; Rivera-Lugo, Yazmin Yorely; Alonso-Núñez, Gabriel; Reynoso-Soto, Edgar A.; et al.
Abstract : New MWCNTs amino-oligoethylene linezolid conjugates having outstanding activity against Gram negative strains. Abstract : Nowadays, infectious diseases caused by drug-resistant bacteria have become especially important. Linezolid is an antibacterial drug active against clinically important Gram positive strains; however, resistance showed by these bacteria has been reported. Nanotechnology has improved a broad area of science, such as medicine, developing new drug delivery and transport systems. In this work, several covalently bounded conjugated nanomaterials were synthesized from multiwalled carbon nanotubes (MWCNTs), a different length oligoethylene chain ( S n ), and two linezolid precursors (4 and 7 ), and they were evaluated in antibacterial assays. Interestingly, due to the intrinsic antibacterial activity of the amino-oligoethylene linezolid analogues, these conjugated nanomaterials showed significant antibacterial activity against various tested bacterial strains in a radial diffusion assay and microdilution method, including Gram negative strains as Escherichia coli (11 mm, 6.25 μg mL −1 ) and Salmonella typhi (14 mm, ≤0.78 μg mL −1 ), which are not inhibited by linezolid. The results show a significant effect of the oligoethylene chain length over the antibacterial activity. Molecular docking of amino-oligoethylene linezolid analogs shows a more favorable interaction of the S 2 -7 analog in the PTC of E. coli .